UPAYA GREENPEACE DALAM MENGATASI DAMPAK KERUSAKAN LINGKUNGAN AKIBAT PENGOPERASIAN PLTU DI DESA CELUKAN BAWANG KABUPATEN BULELENG PROVINSI BALI - Dina Andha Nur Afrilia; Den Yealta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Currently, about 40% of the electricity generated around the world still comes from coal-fired power plants. Including Bali is known as the largest tourism area in Indonesia. PLTU Celukan Bawang Bali is a coal-fired power plant that has resulted in various socio-economic, environmental and health impacts that harm citizens. Coal burning is the largest source of Green House Gas (GHG) gas emissions, which triggers climate change. These energy sources will exacerbate air quality in Bali and threaten public health, as well as the tourism industry in Bali. Greenpeace as a caring organization began to highlight environmental issues in this area.The purpose of the study is to understand how the role of one international organization in achieving their goal to provide assistance in particular environmental issues. This research theoretically has built with green thought perspectives on International Relations and supported by International Organization theory T.may Rudi and Role Theory. Formulation of all arguments, facts, and theoretical framework on this research is guided by qualitative explanation methods. Technique in this research is through by the study of library. Data which is gotten and collected through the journal books, the last thesis and then from internet has related to the problems. Researcher has formulated answered-hypothesis whic reveals the fact that Greenpeace's efforts to overcome the impact of environmental damage due to the operation of PLTU Celukan Bawang through the campaign